Makna Tajassus dan Ghibah dalam Tafsir Al-Azhar serta Relevansinya terhadap Etika Komunikasi Pesantren Darussalam Siunggam Jae - Tsuibatul Aslamiyah Daulay; Mardian Idris Harahap (Kartika: Jurnal Studi Keislaman, 2026)
This study is motivated by the persistence of unethical communication practices, such as negative suspicion, fault-finding, and speaking ill of others in social interaction, including within Islamic boarding schools. It aims to explain the meaning of tajassus and ghibah in QS. Al-Hujurat [49]: 12 according to Hamka’s interpretation in Tafsir Al-Azhar and to analyze their relevance to communication ethics at Darussalam Siunggam Jae Islamic Boarding School. This research uses a qualitative approach by combining library research and fieldwork. Library data were obtained from Tafsir Al-Azhar and related academic literature, while field data were collected through observation and interviews with the pesantren leader, male and female teachers, and students. The data were analyzed descriptively and thematically. The findings show that Hamka interprets tajassus as the act of seeking others’ faults rooted in negative suspicion, while ghibah is understood as talking about someone’s shortcomings behind their back. Both damage honor, trust, and social harmony. The study implies the need to strengthen pesantren communication ethics through husnuzan, tabayyun, self-control in speech, and moral exemplarity